2007
DOI: 10.1080/14767050701449745
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic and arachidonic acid in perinatal asphyxia and prematurity

Abstract: Perinatal asphyxia is associated with a reduction in LC-PUFA levels, most likely as a result of increased oxidative stress. Premature infants soon after birth have higher LC-PUFA levels than term neonates, probably reflecting the overall metabolic activity and/or intrauterine transport of LC-PUFA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…Indeed, the plasma trienoic acid/tetraenoic acid ratio was less than 0.4 (data not shown), and the EFA status index in RBC (averages from 1.6 to 1.8 all through the study period; data not shown) was relatively close to the values (i.e., 2.1) reported in 26-36 weeks healthy preterm newborns [33]. In addition, the LA concentration of total plasma lipids was in the upper range of values previously published in healthy premature neonates of 26-36 weeks of GA, themselves very similar to values found in healthy full-term newborns (i.e., 90 to 500 mg/L) [34]. The same remark can be made for the ARA concentration of plasma total lipids, which was within the range previously reported (120-270 mg/L) [34].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Indeed, the plasma trienoic acid/tetraenoic acid ratio was less than 0.4 (data not shown), and the EFA status index in RBC (averages from 1.6 to 1.8 all through the study period; data not shown) was relatively close to the values (i.e., 2.1) reported in 26-36 weeks healthy preterm newborns [33]. In addition, the LA concentration of total plasma lipids was in the upper range of values previously published in healthy premature neonates of 26-36 weeks of GA, themselves very similar to values found in healthy full-term newborns (i.e., 90 to 500 mg/L) [34]. The same remark can be made for the ARA concentration of plasma total lipids, which was within the range previously reported (120-270 mg/L) [34].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, the LA concentration of total plasma lipids was in the upper range of values previously published in healthy premature neonates of 26-36 weeks of GA, themselves very similar to values found in healthy full-term newborns (i.e., 90 to 500 mg/L) [34]. The same remark can be made for the ARA concentration of plasma total lipids, which was within the range previously reported (120-270 mg/L) [34]. In the study by Soriano et al [30] that showed no change in plasma LA and ARA levels in premature neonates after massage with soybean, neonates were also not EFA deficient (16-18% LA and 9.4-10% ARA of total FA in total plasma lipids).…”
Section: Discussionsupporting
confidence: 87%
“…The main causes of oxidative stress in the newborn period are associated with oxygen administration [8], mechanical ventilation [9], intermittent hypoxia and apnea episodes [10], and asphyxia [11]. In general, the fetal-to-neonatal transition is characterized by intermittent hypoxia periods, involving over-production of oxidative substances and a disequilibrium in important cellular pathways, such as oxidation or inflammation biomolecules [12].…”
Section: Oxidative Stress In Preterm Infantsmentioning
confidence: 99%
“…Unfortunately, relatively few of these interventions have been found to be effective. Although low plasma concentrations of long‐chain polyunsaturated fatty acids have been documented in asphyxiated and infants born preterm, a systematic review of long‐chain polyunsaturated fatty acids supplementation in infants born preterm did not find any evidence of benefit …”
mentioning
confidence: 98%